Radio Broadcasting Experience and Development Prospects (European Scientific Dialogue) - A. Ryazantsev, Vadim; V. Polonskiy, Andrey; I. Karpenko, Irina; I. Radchenko, Elena; M. Narozhnyaya, Svetlana (International Journal of Criminology and Sociology, 2022)
The paper presents an analysis of various opinions concerning radio-industry development issues, given new IT processes implemented in mass media. The authors study the technological evolution of radio broadcasting in terms of analyzing its main development stages. They provide an assessment of listeners’ high confidence in radio broadcasts as compared to other mass media sources. Focus is placed on promoting sonic brands in the sphere of media-communication. The researchers also pay special attention to podcasting as a new way to listen to audio-content. The advantages and possible consequences of podcasting influence on radio-industry are assessed. The research is based on the expert discussion on radio broadcasting issues which took place at “Radiodays Europe 2019”.